Water flow control for optimal operation of air to water heat exchanger - Muhammad Nurul Irfan Abdul Aziz (2014)
Chilled beam systems are considered to be energy efficient and have the ability to provide sensible cooling in a given space. Active chilled beam systems (ACB) will be the primary focus over the passive system due to the higher cooling efficiency. ACB consists of chilled water pipes and an integral air supply unit. This is to create force induction of air in the room and the reconditioned air will be cooled again upon mixing with the primary air. Consideration of the flow and temperature of the chilled water has to be taken into account so as to prevent condensation from occurring.